Cx43 Inhibition Attenuates Sepsis-Induced Intestinal Injury via Downregulating ROS Transfer and the Activation of the JNK1/Sirt1/FoxO3a Signaling Pathway - Zhaowei Zou; Bin Liu; Lisi Zeng; Xianzi Yang; Renli Huang; Cheng Wu; Huijuan Zhu; Yi Gao; Dongdong Yuan; Jinlong Yu (Mediators of Inflammation)
Intestinal injury has long been considered to play a crucial role in the pathophysiology of sepsis and has even been characterized as the “motor” of it. Thus, we explored the effects of connexin43 (Cx43) on sepsis-induced intestinal injury in order to provide potential therapeutic strategies. Rat cecal ligation and puncture (CLP) models in vivo and cell models (IEC-6 cells) pretreated with LPS in vitro were used in the current study. Firstly, different methods, such as Cx43 inhibitors (18-α-GA and oleamide) or siRNA targeting Cx43 and N-acetyl cysteine (NAC) (a kind of ROS scavenger), were used to observe the effects of Cx43 channels mediating ROS transfer on intestinal injury. Secondly, the influence of ROS content on the activity of the JNK1/Sirt1/FoxO3a signaling pathway was explored through the application of NAC, sp600125 (a JNK1 inhibitor), and nicotinamide (a Sirt1 inhibitor). Finally, luciferase assays and ChIP were used to determine the direct regulation of FoxO3a on proapoptotic proteins, Bim and Puma. The results showed that sepsis-induced intestinal injury presented a dynamic change, coincident with the alternation of Cx43 expression. The inhibition of Cx43 attenuated CLP-induced intestinal injury in vivo and LPS-induced IEC-6 injury in vitro. The changes of Cx43 channel function regulated ROS transfer between the neighboring cells, which mediated the activation of the JNK1/Sirt1/FoxO3a signaling pathway. FoxO3a directly affected its downstream target genes, Bim and Puma, which are responsible for cell or tissue apoptosis. In summary, our results suggest that Cx43 inhibition suppresses ROS transfer and inactivates the JNK1/Sirt1/FoxO3a signaling pathway to protect against sepsis-induced intestinal injury.